2021
DOI: 10.3389/fonc.2021.628127
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine With or Without Micro-Transplantation for the Treatment of Intermediate or High-Risk Myelodysplastic Syndrome: A Chinese Single-Center Retrospective Study of 22 Patients

Abstract: The treatment outcomes of intermediate or high-risk myelodysplastic syndrome (MDS) remain unsatisfactory. This study was designed to evaluate the safety and efficacy of human leukocyte antigen (HLA)-mismatched hematopoietic stem cell micro-transplantation (MST) in patients with MDS. A total of 22 patients with MDS, ranging between the ages of 39 and 74, were enrolled in this study. Eleven patients were given decitabine (DAC), a DNA methyltransferase inhibitor, combined with HLA-mismatched MST (MST-DAC group), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The report by Li et al. also showed that DAC combined with MST could increase the overall response rate ( 40 ). This is a new scheme of DAC combined with micro-transplantation (MST), which can effectively prolong the survival of patients with high-risk MDS and TAML, especially for MDS patients, and may become an effective bridging method for allogeneic transplantation.…”
Section: During Hsctmentioning
confidence: 97%
“…The report by Li et al. also showed that DAC combined with MST could increase the overall response rate ( 40 ). This is a new scheme of DAC combined with micro-transplantation (MST), which can effectively prolong the survival of patients with high-risk MDS and TAML, especially for MDS patients, and may become an effective bridging method for allogeneic transplantation.…”
Section: During Hsctmentioning
confidence: 97%
“…The WT1 is a tumor marker found in leukemic blasts 27 and is closely associated with a poorer long‐term prognosis in AML. In our previous studies, 28 , 29 WT1 transcript levels proved to be effective in assessing disease progression in patients with MDS (including CMML). In this study, we also found a strong correlation between changes in WT1 mRNA and treatment response which indicates the effectiveness of Vene combination therapy indirectly.…”
Section: Discussionmentioning
confidence: 99%